Carbon nanomaterial loaded fiber and preparation method thereof

By loading carbon nanomaterial dispersion on the fiber surface and processing it in a solidification bath, the problem of insufficient interfacial binding force is solved, and carbon nanomaterial loaded fibers with excellent conductivity and low cost are achieved, ensuring high purity and stability.

CN119265925AActive Publication Date: 2025-01-07SUZHOU INST OF NANO TECH & NANO BIONICS CHINESE ACEDEMY OF SCI

Patent Information

Application Number
CN202411394071.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-07
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

When the prior art imparts electrical and thermal conductivity to fibers, the introduction of metal coating increases material density and weakens corrosion resistance. In addition, the interface bonding force of carbon nanomaterial loaded fibers is insufficient, and the purity of composite materials is affected.

Method used

The carbon nanomaterial dispersion is loaded with the fiber surface and treated in a solidification bath. The dispersion of the dispersant is used to enhance the interface interaction, and achieve uniform and firm coating of the carbon nanomaterials, avoiding the use of auxiliary additives.

Benefits of technology

It realizes carbon nanomaterial loaded fibers with excellent conductivity, which are low-cost, high purity, strong load capacity, good stability, and no complex dispersion formulation is required.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265925A_ABST
    Figure CN119265925A_ABST
Patent Text Reader

Abstract

The invention provides a carbon nanomaterial loaded fiber and a preparation method thereof, and the preparation method comprises the following steps: mixing a carbon nanomaterial, a dispersant and a solvent, and dispersing to obtain a carbon nano dispersion liquid; loading the carbon nano dispersion liquid on the surface of a fiber to obtain a carbon nano dispersion liquid loaded fiber; and carrying out coagulating bath treatment on the carbon nano dispersion liquid loaded fiber, and drying to obtain the carbon nano material loaded fiber. The loading method of the carbon nanomaterial provided by the invention is simple and efficient, low in cost and free of a complex dispersion liquid formula, and the obtained carbon nanomaterial loaded fiber is high in purity, does not contain other auxiliary additives except the carbon nanomaterial and the fiber, and is strong in coating force and good in stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials and relates to a carbon nano material loaded fiber, in particular to a carbon nano material loaded fiber and a preparation method thereof. Background Art

[0002] Fiber materials, such as glass fibers, have excellent mechanical properties, chemical stability and special functionality, and are widely used in aerospace, industry, medical and other fields. With the continuous advancement of science and technology, the demand for functionalization of fibers is also growing, especially while maintaining their traditional advantages such as light weight, high strength, heat resistance and corrosion resistance, giving them new functional properties, such as electrical conductivity and thermal conductivity, to further broaden their application areas.

[0003] To achieve this goal, researchers have tried to coat the fiber surface with a layer of metal coating through chemical plating, sputtering, etc. Although this method can indeed give the fiber conductive properties, the problems that come with it cannot be ignored. For example, the introduction of metal materials not only greatly increases the density of the material, but also weakens its corrosion resistance to a certain extent, which undoubtedly limits its application in more fields.

[0004] In order to overcome the above limitations, researchers have turned to carbon nanomaterials, such as carbon nanotubes (CNTs) and graphene. These carbon nanomaterials have become an ideal solution due to their excellent electrical and thermal conductivity and chemical stability. They can give the fiber electrical and thermal conductivity without damaging its original properties, thus greatly broadening the application range of the fiber.

[0005] At present, there are many methods to realize the loading of carbon nanomaterials on the fiber surface, such as chemical vapor deposition (CVD), spraying or coating. For example, CN108330679A discloses a method for preparing a graphene-coated conductive fiber, wherein graphene oxide is reduced to form a graphene hydrosol, and the fiber is uniformly coated with the impregnation and pulling method. The fiber materials loaded with graphene disclosed in CN108774879A, CN111808314A, etc., make the loading of graphene on the fiber be realized by forming opposite charges between the loading material and the fiber, and then impregnating, and realizing the loading of graphene on the fiber through electrostatic self-assembly. CN109267325A discloses a graphene / nanomaterial coated fiber with uniform surface dispersion and a method for preparing the same, wherein the graphene oxide is first mechanically stirred and crushed in an ice-water bath to obtain uniformly dispersed graphene oxide, and then impregnated. In the methods of carbon material loading fiber disclosed in the prior art, on the one hand, the interface bonding strength between the carbon loaded fiber and the fiber obtained by coating, impregnating and drying alone is insufficient; on the other hand, if the interface bonding strength is to be enhanced, it is often necessary to rely on the formulation of carbon nano-solutions and the addition of auxiliary additives such as ionic groups, which results in a complicated process and has a certain impact on the purity of the composite material.

[0006] Therefore, based on the deficiencies in the prior art, the present invention provides a carbon nanomaterial-loaded fiber and a preparation method thereof. Summary of the invention

[0007] The purpose of the present invention is to provide a carbon nanomaterial loaded fiber and a preparation method thereof. The preparation method is simple, efficient and low-cost. The obtained carbon nanomaterial loaded fiber does not contain other auxiliary additives and has excellent conductive properties.

[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing carbon nanomaterial-loaded fibers, the preparation method comprising the following steps:

[0010] (1) mixing and dispersing a carbon nanomaterial, a dispersant and a solvent to obtain a carbon nano dispersion;

[0011] (2) loading the carbon nano-dispersion on the fiber surface to obtain carbon nano-dispersion loaded fibers;

[0012] (3) subjecting the carbon nanomaterial-loaded fiber to a coagulation bath treatment and drying to obtain the carbon nanomaterial-loaded fiber.

[0013] The preparation method provided by the present invention prepares a carbon nano material into a dispersion liquid, combines a two-step process of loading and a coagulation bath, and loads the carbon nano material on a fiber material. During the loading process, the dispersion liquid formed by the carbon nano material is evenly coated on the fiber surface, and then the dispersant is dissolved in the coagulation bath by utilizing the difference in solubility of the dispersant in the dispersion liquid system and the coagulation system, so that a strong interaction is formed between the carbon nano materials, and the carbon nano materials are completely and firmly coated on the fiber surface. The preparation method provided by the present invention is simple and efficient, low in cost, does not require a complex dispersion liquid formula, and the used dispersant is removed in the coagulation bath. The obtained carbon nano material-loaded fiber has high purity, does not contain other auxiliary additives except the carbon nano material and the fiber, and has a strong coating force and good stability.

[0014] Preferably, the carbon nanomaterial in step (1) comprises any one of carbon nanotubes, carbon black, graphene, graphene oxide or nanographene sheets, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of carbon nanotubes and carbon black, a combination of carbon black and graphene, a combination of graphene and graphene oxide, a combination of graphene oxide and nanographene sheets, a combination of carbon nanotubes, carbon black and graphene, a combination of carbon black, graphene and graphene oxide, or a combination of carbon nanotubes, carbon black, graphene and graphene oxide.

[0015] Preferably, the carbon nanotubes include single-walled carbon nanotubes and / or multi-walled carbon nanotubes.

[0016] Preferably, the median length of the carbon nanotubes is 0.1-1000 μm, for example, it can be 0.1 μm, 0.5 μm, 1 μm, 5 μm, 10 μm, 30 μm, 50 μm, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm, 500 μm, 600 μm, 700 μm, 800 μm, 900 μm or 1000 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, preferably 1-800 μm, and more preferably 10-500 μm.

[0017] Preferably, the flake diameter of the graphene or graphene oxide is 0.1-2000 μm, for example, it can be 0.1 μm, 0.5 μm, 1 μm, 5 μm, 10 μm, 30 μm, 50 μm, 80 μm, 100 μm, 120 μm, 150 μm, 180 μm, 200 μm, 400 μm, 500 μm, 600 μm, 800 μm, 1000 μm, 1200 μm, 1500 μm, 1800 μm or 2000 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, preferably 1-1000 μm, and more preferably 5-200 μm.

[0018] Preferably, the dispersant in step (1) comprises an ionic surfactant and / or a non-ionic surfactant.

[0019] Preferably, the dispersant in step (1) comprises any one of alkyl aryl phosphates, alkyl benzene sulfonates, dialkyl sulfosuccinates, polyoxyethylene alkylphenol ethers, sorbitol alkylates, polycarboxylates, polymethacrylic acid derivatives, maleic anhydride copolymer quaternary ammonium salts, pyridinium hydrochloride or phosphate ester salts, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of alkyl aryl phosphates and alkyl benzene sulfonates, a combination of dialkyl sulfosuccinates and polyoxyethylene alkylphenol ethers, a combination of sorbitol alkylates and polycarboxylates, a combination of polymethacrylic acid derivatives and maleic anhydride copolymer quaternary ammonium salts, or a combination of pyridinium hydrochloride and phosphate ester salts.

[0020] Preferably, the mass ratio of the dispersant to the carbon nanomaterial in step (1) is (0.1-10):1, for example, it can be 0.1:1, 0.2:1, 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or 10:1, preferably (0.2-5):1, and more preferably (0.5-3):1.

[0021] Preferably, the dispersing method in step (1) comprises any one of stirring, ultrasound, homogenization, sand milling or emulsification, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of stirring and ultrasound, a combination of ultrasound and homogenization, a combination of homogenization and sand milling, a combination of sand milling and emulsification, a combination of stirring, ultrasound and homogenization, or a combination of homogenization, sand milling and emulsification.

[0022] Preferably, the concentration of the carbon nanomaterial in the carbon nano dispersion in step (1) is 0.1-50 g / L, for example, it can be 0.1 g / L, 0.2 g / L, 0.5 g / L, 1 g / L, 5 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L, 35 g / L, 40 g / L, 45 g / L or 50 g / L, but is not limited to the listed values. Other values ​​not listed in the numerical range are also applicable, preferably 0.5-20 g / L, and more preferably 1-10 g / L.

[0023] Preferably, the surface tension of the carbon nano dispersion in step (1) is 21-52 mN / m, for example, it can be 21 mN / m, 25 mN / m, 30 mN / m, 35 mN / m, 40 mN / m, 45 mN / m, 50 mN / m or 52 mN / m, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0024] Preferably, the viscosity of the carbon nano dispersion in step (1) is 10-10000 mPa·s, for example, it can be 10 mPa·s, 50 mPa·s, 100 mPa·s, 500 mPa·s, 1000 mPa·s, 1500 mPa·s, 2000 mPa·s, 2500 mPa·s, 3000 mPa·s, 3500 mPa·s, 4000 mPa·s, 4500 mPa·s, 5000 mPa·s, 6000 mPa·s, 7000 mPa·s, 8000 mPa·s, 9000 mPa·s or 10000 mPa·s, preferably 100-5000 mPa·s.

[0025] Preferably, the fibers in step (2) include organic fibers and / or inorganic fibers.

[0026] Preferably, the organic fiber includes any one of polyester, acrylic, nylon, polypropylene, aramid, polyethylene fiber, poly(p-phenylene benzobisoxazole) fiber (PBO fiber), poly(p-benzimidazole) fiber (PBI fiber), poly(phenylene pyridine diimidazole) fiber (M5 fiber) or polyimide fiber (PI fiber), or a combination of at least two thereof.

[0027] Preferably, the inorganic fiber includes any one of glass fiber, quartz fiber, basalt fiber, ceramic fiber, alumina fiber, aluminum silicate fiber, mullite fiber or silicon carbide fiber, or a combination of at least two thereof.

[0028] Preferably, the fibers include any one of fiber monofilaments, fiber tows, fiber unidirectional fabrics, fiber non-woven fabrics, or fiber woven fabrics, or a combination of at least two of them.

[0029] Preferably, the fiber woven cloth includes but is not limited to any one of fiber plain cloth, fiber twill cloth or fiber satin cloth, or a combination of at least two of them.

[0030] Preferably, the loading method in step (2) includes any one of dipping, spraying or spin coating or a combination of at least two of them. Typical but non-limiting combinations include a combination of dipping and spraying, a combination of spraying and spin coating, a combination of dipping and spin coating, or a combination of dipping, spraying and spin coating.

[0031] Preferably, the loading time in step (2) is ≥10s, for example, it can be 10s, 20s, 30s, 1min, 2min, 3min, 4min, 5min, 6min, 8min, 10min, 15min, 20min or 30min, but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable, preferably ≥1min, and more preferably ≥2min.

[0032] Preferably, the medium of the coagulation bath in step (3) comprises any one of an alcohol compound, a ketone compound, an ether compound, an ester compound or an aqueous solution, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of an alcohol compound and a ketone compound, a combination of a ketone compound and an ether compound, a combination of an ether compound and an ester compound, a combination of an ester compound and an aqueous solution, a combination of an alcohol compound, a ketone compound and an ether compound, or a combination of an ether compound, an ester compound and an aqueous solution.

[0033] Preferably, the medium of the coagulation bath in step (3) comprises any one of butanol, pentanol, ethanol, polyethylene glycol, acetone, ethylene glycol butyl ether, ethyl acetate, sodium sulfate aqueous solution or deionized water, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of butanol and pentanol, a combination of ethanol and polyethylene glycol, a combination of polyethylene glycol and acetone, a combination of ethylene glycol butyl ether and ethyl acetate, a combination of ethyl acetate and sodium sulfate aqueous solution, a combination of pentanol, ethanol and polyethylene glycol, or a combination of acetone, ethylene glycol butyl ether, ethyl acetate and sodium sulfate aqueous solution.

[0034] Preferably, the time of the coagulation bath in step (3) is ≥30 s, for example, it can be 30 s, 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 12 min, 14 min, 15 min, 16 min, 18 min, 20 min, 22 min, 24 min, 25 min, 26 min, 28 min or 30 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, preferably ≥2 min, and more preferably ≥4 min.

[0035] In a second aspect, the present invention provides a carbon nanomaterial-loaded fiber, wherein the carbon nanomaterial-loaded fiber is prepared by the preparation method described in the first aspect.

[0036] Preferably, the square resistance of the carbon nanomaterial-loaded fiber is 0.5-5000Ω / □, for example, it can be 0.5Ω / □, 1Ω / □, 5Ω / □, 10Ω / □, 50Ω / □, 100Ω / □, 300Ω / □, 500Ω / □, 800Ω / □, 1000Ω / □, 1200Ω / □, 1500Ω / □, 2000Ω / □, 2500Ω / □, 3000Ω / □, 3500Ω / □, 4000Ω / □, 4500Ω / □ or 5000Ω / □, but is not limited to the listed values, and other values ​​not listed within the numerical range are equally applicable.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] The carbon nanomaterial loading method provided by the present invention is simple, efficient, low-cost, does not require a complex dispersion liquid formula, and the obtained carbon nanomaterial loaded fiber has high purity and does not contain other auxiliary additives except the carbon nanomaterial and the fiber. The loaded fiber has strong coating force and good stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 is a scanning electron microscope image of the glass fiber of Example 6;

[0040] Figure 2 This is a scanning electron microscope image of the carbon nanomaterial-loaded fiber provided in Example 6. DETAILED DESCRIPTION

[0041] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0042] Example 1

[0043] This embodiment provides a method for preparing carbon nanomaterial-loaded fibers, the preparation method comprising the following steps:

[0044] (1) adding 0.3 g of polyvinyl pyrrolidone and 0.1 g of single-walled carbon nanotubes to 100 mL of water, wherein the median length of the single-walled carbon nanotubes is 20 μm, and performing ultrasonic dispersion for 30 min to obtain a single-walled carbon nanotube dispersion, wherein the concentration of the carbon nanomaterial in the dispersion is 1 g / L, the viscosity of the dispersion is 740 mPa·s, and the surface tension of the system is 35 mN / m, and then soaking a glass fiber plain weave cloth in the obtained dispersion for 10 min, wherein the carbon nanotubes are loaded on the surface of the glass fiber cloth, and a dispersion-loaded glass fiber cloth is obtained;

[0045] (2) placing the loaded glass fiber cloth into an ethanol coagulation bath for 5 minutes, taking it out and drying it to obtain the carbon nanomaterial loaded fiber.

[0046] Example 2

[0047] This embodiment provides a method for preparing carbon nanomaterial-loaded fibers, the preparation method comprising the following steps:

[0048] (1) adding 0.1 g of polyvinyl pyrrolidone and 1 g of graphene to 100 mL of water, wherein the median sheet diameter of the graphene is 2000 μm, and treating the mixture in a 200 bar high-pressure homogenizer for 20 min to obtain a graphene dispersion, wherein the concentration of the carbon nanomaterial in the dispersion is 50 g / L, the viscosity of the dispersion is 9986 mPa·s, and the surface tension of the dispersion is 48 mN / m, and then immersing an aramid fiber tow in the dispersion for 30 seconds, wherein the graphene is loaded on the surface of the aramid fiber, and an aramid fiber tow loaded with the dispersion is obtained;

[0049] (2) placing the loaded aramid fiber tow into an acetone coagulation bath for 30 seconds, taking it out and drying it to obtain the carbon nanomaterial loaded fiber.

[0050] In this embodiment, the obtained carbon nanomaterial-loaded fibers are woven into plain cloth.

[0051] Example 3

[0052] This embodiment provides a method for preparing carbon nanomaterial-loaded fibers. Compared with Embodiment 1, the immersion time in step (1) is controlled to be 30 seconds, and the rest is the same as Embodiment 1.

[0053] Example 4

[0054] This embodiment provides a method for preparing carbon nanomaterial-loaded fibers. Compared with Embodiment 1, the coagulation time of step (2) is controlled to be 2 minutes, and the rest is the same as Embodiment 1.

[0055] Example 5

[0056] This embodiment provides a method for preparing carbon nanomaterial-loaded fibers. Compared with Embodiment 1, the concentration of the carbon nanomaterial in the dispersion in step (1) is 0.1 g / L, and the rest is the same as Embodiment 1.

[0057] Example 6

[0058] This embodiment provides a method for preparing carbon nanomaterial-loaded fibers. Compared with Embodiment 1, the concentration of the carbon nanomaterial in the dispersion in step (1) is 0.5 g / L, and the rest is the same as Embodiment 1.

[0059] Example 7

[0060] This embodiment provides a method for preparing carbon nanomaterial-loaded fibers. Compared with Embodiment 1, the mass of the dispersant in step (1) is replaced by sodium dodecylbenzene sulfonate, and the rest is the same as Embodiment 1.

[0061] Example 8

[0062] This embodiment provides a method for preparing carbon nanomaterial-loaded fibers. Compared with Embodiment 1, the medium of the coagulation bath in step (2) is replaced with ethyl acetate, and the rest is the same as Embodiment 1.

[0063] Example 9

[0064] This embodiment provides a method for preparing carbon nanomaterial-loaded fibers. Compared with Embodiment 1, in step (2), the medium of the coagulation bath is replaced with a sodium sulfate aqueous solution, and the concentration of the sodium sulfate aqueous solution is 25%. The rest is the same as Embodiment 1.

[0065] Example 10

[0066] This embodiment provides a method for preparing carbon nanomaterial-loaded fibers. Compared with Embodiment 1, the medium of the coagulation bath in step (2) is replaced with sulfuric acid, and the rest is the same as Embodiment 1.

[0067] Comparative Example 1

[0068] This comparative example provides a method for preparing carbon nanomaterial-loaded fibers. Compared with Example 1, the coagulation bath treatment in step (2) is not performed, that is, the glass fibers loaded with the dispersion in step (1) are directly dried to obtain the carbon nanomaterial-loaded fibers. The rest is the same as Example 1.

[0069] Comparative Example 2

[0070] This comparative example provides a method for preparing carbon nanomaterial-loaded fibers. Compared with Example 1, no dispersant is added in step (1), and the rest is the same as Example 1.

[0071] The carbon nanomaterial loaded fibers obtained in the examples and comparative examples were subjected to electrical property tests using four probes. The uniformity of the load was determined by testing the square resistance of different regions of the material and calculating the relative error. The load stability was evaluated by flushing the loaded fiber surface with 1 MPa water pressure and calculating the change in square resistance before and after. The results are listed in Table 1.

[0072] Table 1

[0073]

[0074] Figure 1 and Figure 2 These are the glass fibers before and after being loaded with the carbon nanomaterial provided in Example 6. It can be seen from the figures that the carbon nanomaterial is uniformly loaded on the surface of the glass fiber and is tightly combined.

[0075] As can be seen from Table 1, the concentration of carbon nanomaterials, loading time and coagulation time are all key factors for regulating the electrical properties, loading uniformity and stability of the fiber surface. Specifically, compared with Example 1, in Examples 5-7, the concentration of carbon nanomaterials and their stable dispersion state in water are directly related to the fluctuation of the resistance value and the uniformity of its distribution; in Example 3, when the duration of the loading process is insufficient, it is easy to cause uneven distribution of the load on the fiber; in Example 4, the control of the coagulation time is also crucial. If the time is too short, it will affect the effective replacement of the dispersant and the close accumulation of carbon nanomaterials on the fiber surface, thereby weakening its electrical performance and overall stability; at the same time, in Examples 8-10, the specific combination of the dispersant and the coagulation bath medium also directly affects the loading effect of the carbon nanomaterial. Different combinations will affect the replacement speed and degree of the dispersion system, thereby affecting the loading of the carbon nanomaterial on the fiber surface.

[0076] In summary, the carbon nanomaterial loading method provided by the present invention is simple, efficient, low-cost, does not require a complex dispersion liquid formula, and the obtained carbon nanomaterial-loaded fibers have high purity and do not contain other auxiliary additives except carbon nanomaterials and fibers. Moreover, the loaded fibers have strong coating force and good stability.

[0077] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing carbon nanomaterial-loaded fibers, characterized in that: The preparation method comprises the following steps: (1) mixing and dispersing a carbon nanomaterial, a dispersant and a solvent to obtain a carbon nano dispersion; (2) loading the carbon nano-dispersion on the fiber surface to obtain carbon nano-dispersion loaded fibers; (3) subjecting the carbon nanomaterial-loaded fiber to a coagulation bath treatment and drying to obtain the carbon nanomaterial-loaded fiber.

2. The preparation method according to claim 1, characterized in that: The carbon nanomaterial in step (1) includes any one of carbon nanotubes, carbon black, graphene, graphene oxide or nanographene sheets, or a combination of at least two thereof; Preferably, the carbon nanotubes include single-walled carbon nanotubes and / or multi-walled carbon nanotubes; Preferably, the median length of the carbon nanotubes is 0.1-1000 μm, preferably 1-800 μm, and more preferably 10-500 μm; Preferably, the flake diameter of the graphene or graphene oxide is 0.1-2000 μm, preferably 1-1000 μm, and more preferably 5-200 μm.

3. The preparation method according to claim 1 or 2, characterized in that: The dispersant in step (1) comprises an ionic surfactant and / or a non-ionic surfactant; Preferably, the dispersant in step (1) comprises any one or a combination of at least two of alkyl aryl phosphates, alkyl benzene sulfonates, dialkyl sulfosuccinates, polyoxyethylene alkylphenol ethers, sorbitol alkylates, polycarboxylates, polymethacrylic acid derivatives, quaternary ammonium salts of maleic anhydride copolymers, pyridinium hydrochloride or phosphate salts; Preferably, the mass ratio of the dispersant to the carbon nanomaterial in step (1) is (0.1-10):1, preferably (0.2-5):1, and more preferably (0.5-3):

1.

4. The preparation method according to any one of claims 1 to 3, characterized in that The dispersion method in step (1) includes any one of stirring, ultrasound, homogenization, sand milling or emulsification, or a combination of at least two of them.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The concentration of the carbon nanomaterial in the carbon nanodispersion liquid in step (1) is 0.1-50 g / L, preferably 0.5-20 g / L, and more preferably 1-10 g / L; Preferably, the surface tension of the carbon nano dispersion in step (1) is 21-52 mN / m; Preferably, the viscosity of the carbon nano-dispersion liquid in step (1) is 10-10000 mPa·s, preferably 100-5000 mPa·s.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The fibers in step (2) include organic fibers and / or inorganic fibers; Preferably, the organic fiber includes any one of polyester, acrylic, nylon, polypropylene, aramid, polyethylene fiber, poly(p-phenylene benzobisoxazole) fiber, poly(p-benzimidazole) fiber, poly(phenylene pyridine diimidazole) fiber or polyimide fiber, or a combination of at least two thereof; Preferably, the inorganic fiber includes any one of glass fiber, quartz fiber, basalt fiber, ceramic fiber, alumina fiber, aluminum silicate fiber, mullite fiber or silicon carbide fiber, or a combination of at least two thereof.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The loading method in step (2) includes any one of dipping, spraying or spin coating or a combination of at least two thereof; Preferably, the loading time in step (2) is ≥10 s, preferably ≥1 min, and more preferably ≥2 min.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The medium of the coagulation bath in step (3) comprises any one of an alcohol compound, a ketone compound, an ether compound, an ester compound or an aqueous solution, or a combination of at least two thereof; Preferably, the medium of the coagulation bath in step (3) comprises any one or a combination of at least two of butanol, pentanol, ethanol, polyethylene glycol, acetone, ethylene glycol butyl ether, ethyl acetate, sodium sulfate aqueous solution or deionized water; Preferably, the coagulation bath time in step (3) is ≥30 s, preferably ≥2 min, and more preferably ≥4 min.

9. A carbon nanomaterial-loaded fiber, characterized in that: The carbon nanomaterial-loaded fiber is prepared by the preparation method according to any one of claims 1 to 8.

10. The carbon nanomaterial-loaded fiber according to claim 9, characterized in that: The square resistance of the carbon nanomaterial-loaded fiber is 0.5-5000Ω / □.

Citation Information

Patent Citations

  • Preparation method of graphene coated electric-conductive fiber

    CN108330679A

  • Preparation method of graphene coating conductive fiber

    CN108774879A

  • Preparation method and application of polyester material loaded with graphene oxide

    CN111808314A

  • Method for preparing continuous cellulose / carbon nanomaterial aerogel fibers through post-supporting of carbon nanomaterials

    CN106012501A

  • Conductive fiber preparation method based on carbon nano-tubes

    CN106223013A

Cited By

  • Carbon nanomaterial-loaded fiber and preparation method therefor

    WO2026076871A1